Early recurrent arrhythmias after out-of-hospital cardiac arrest associated with obstructive coronary artery disease: Analysis of the PROCAT registry. (August 2019) - Bellut, Hugo; Guillemet, Lucie; Bougouin, Wulfran; Charpentier, Julien; Ben Hadj Salem, Omar; Llitjos, Jean-François; Paul, Marine; Valade, Sandrine; Spagnolo, Shirley; Lamhaut, Lionel; Chiche, Jean-Daniel; Marijon, Eloi; et al.
Abstract: Objective: After out-of-hospital cardiac arrest (OHCA) associated with obstructive coronary artery disease (CAD), the risk of recurrence during the early period is unclear and the indication for anti-arrhythmic treatment is debated. We assessed the incidence and predisposing factors for severe cardiac arrhythmias in this population. Design: Retrospective study in a cardiac arrest center. Settings: The primary endpoint was the occurrence of major cardiac arrhythmias from hospital admission to intensive care unit (ICU) discharge in patients admitted after an OHCA associated with obstructive CAD. A major arrhythmia was defined as any arrhythmic event (auricular or ventricular) associated with cardiac arrest recurrence and/or severe arterial hypotension. Secondary outcomes were time from ICU admission to arrhythmia occurrence and all-cause in-ICU mortality. Risk factors for recurrence of a major arrhythmia were assessed using multivariate analysis. Patients: We included all consecutive OHCA patients resuscitated from ventricular fibrillation (VF) or pulseless ventricular tachycardia (VT) as initial rhythm associated with obstructive CAD, and who had a successful primary percutaneous coronary intervention. Intervention: None. Measurements and main results: Among 256 patients, a major arrhythmia occurred in 29 (11.3%), within the first 24 h in 79.3% of cases and were mostly VF (44.8%). Mortality rate was significantly increased in patients with major arrhythmia recurrence (69% vs 41%; p = 0.006). Factor significantly associated with recurrence of severe arrhythmia was male gender (OR 0.32 [0.12–0.92]; p = 0.034). Treatment with prophylactic anti-arrhythmic in the ICU was not associated with a change in the risk of recurrence (OR 0.85 [0.21–3.65], p = 0.82). Conclusion: An early recurrence of major arrhythmia was observed in more than 10% of post-cardiac arrest patients. These events happened mostly within the first 24 h. The interest of prophylactic anti-arrhythmic treatment remains to be evaluated in this population.